2023
DOI: 10.15516/cje.v25i1.4591
|View full text |Cite
|
Sign up to set email alerts
|

Representations of National Identity in the Methodological Apparatus/Structure of Science & Social Studies Textbooks in the LowerGrades of Primary School /Nacionalni identitet u metodičkom instrumentariju udžbenika iz prirode i društva u nižim razredima osnovne škole

Abstract: This paper presents the results of the research conducted with the aim of examining the frequency and development of the components of national identity in the methodological instrumentation of Science Social Studies textbooks in the first cycle of primary education in Serbia. Starting from the assumptions of the integrative developmental-contextual theory of Bar-Tal and Teichmann, Barrett’s societal-social-cognitive-motivational theory, as well as previous research, national identity is operationalized withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For example, Danijela et al classified the representation of national identity education in textbooks into 12 aspects, such as family, religion, language and so on, based on integrative developmental-contextual theory and societal-social-cognitive-motivational theory. The textbooks for the lower grades of primary school in Serbia were found to be under-represented in terms of family, religion, language and 12 other aspects of national identity education, and there were problems with the dynamics and continuity of the representations [27]. Research has also shown that study tours are an important way of promoting national identity education, with visits to historical sites and famous landscapes having a direct impact on students' cognition, emotions and behaviour [28].…”
Section: Literature Review 21 National Identity Educationmentioning
confidence: 99%
“…For example, Danijela et al classified the representation of national identity education in textbooks into 12 aspects, such as family, religion, language and so on, based on integrative developmental-contextual theory and societal-social-cognitive-motivational theory. The textbooks for the lower grades of primary school in Serbia were found to be under-represented in terms of family, religion, language and 12 other aspects of national identity education, and there were problems with the dynamics and continuity of the representations [27]. Research has also shown that study tours are an important way of promoting national identity education, with visits to historical sites and famous landscapes having a direct impact on students' cognition, emotions and behaviour [28].…”
Section: Literature Review 21 National Identity Educationmentioning
confidence: 99%